The Impact of Intraoperative Hyperlactatemia on Weaning from Cardiopulmonary Bypass in Patients Undergoing on-Pump Coronary Artery Bypass Grafting Surgery: An Observational Study - Pierre Zarif Tawadros; Mahmoud Mohamed Mustafa; Amr Abdelmonem Ibrahim; Hadi El-Masry; Mostafa A. Al-Tantawy (Bali Journal of Anesthesiology)
Background: Hyperlactatemia after cardiac surgery is common. However, the association and the implications of hyperlactatemia on the prognosis after cardiopulmonary bypass (CPB) remains controversial. This study investigated the associations between early-onset hyperlactatemia and the need for doses of inotropes and vasopressors during weaning from CPB, hemodynamic stability after weaning from CPB, and the duration of postoperative mechanical ventilation.